PENGARUH KEPEMIMPINAN TRANSFORMASIONAL IKLIM ORGANISASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PERGURUAN TINGGI SWASTA DI KOTA BIMA - Muhammad yusuf; Zainal Abidin; Siti Nurmayanti (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2017)
This research is aimed at determining the effect of transformational leadership, organizational environment and work discipline on the performance of private universities employees in Bima. The analysis is also to determine dominant variable affecting the performance of employees performance. This research is causal associative. The population is the employees of all universities in Bima from which 69 respondent were selected. The data were collected through questionnaires. The test is conducted with validity and reliability test. The data then were analyzed with multiple linear regression along with determination test (R2) t-test (partial), standardized coefficients beta. The research showed that (1). there is significant effect partially of transformational leadership, organizational environment and work discipline on the performance of employees, (2) work discipline is the most dominant affecting variable on the employees performance.Keywords: transformational leadership, organizational environment, work discipline,